Graphene oxide-Laponite hybrid from highly stable aqueous dispersion - Chouhan D.K.; Patro T.U.; Harikrishnan G.; Kumar S.; Gupta S.; Kumar G.S.; Cohen H.; Wagner H.D. (My University, 2025)
A simple method for preparation of hybrid of graphene oxide (GO) and Laponite (Lap), obtained by solvent evaporation from their highly stable aqueous dispersions is reported. The dispersion up to ~ 1 mg/ml of GO in 1% Lap dispersion, i.e., 10:1 of Lap:GO was found to be stable without flocculation for several months; lower mass ratios of Lap to GO than this showed marginal flocculation with time. The electrostatic interaction between cations present in the interlayers of Lap and the functional groups of GO is envisaged to be the cause for the stable dispersion, which was confirmed by the presence of cations; viz., Na+ and small amounts of K+ and Mg2 + in the aqueous filtrate of the hybrid. Their interaction was further confirmed by higher absorption of GO in aqueous Lap dispersion than that in water using UV–vis spectroscopy. The resulting hybrid material was found to be partially reduced and self-assembled to form layered structure in its dry state. The hybrids further showed improved electrical conductivity (~ 0.01 S/cm) upon chemical reduction. The present study demonstrates a facile method for preparation of a new hybrid material and greener pathway for GO reduction; though partially. This hybrid has potential as multifunctional filler for clay polymer nanocomposites. © 2016 Elsevier B.V.